Controllable fabrication and optical properties of Sn-doped ZnO hexagonal microdisk for whispering gallery mode microlaser - J. Dai; C. X. Xu; X. Y. Xu; J. T. Li; J. Y. Guo; Y. Lin (APL Materials, 2013)
We report a controllable method for fabricating hexagonal Sn doped ZnO microdisks. The photoluminescence mechanism of the Sn doped ZnO microdisks is investigated, the defect emission is attributed to the singly charged oxygen vacancy. Under the excitation of a femtosecond pulsed laser with a wavelength of 325 nm, exciton-exciton collision process is clearly demonstrated, and amplified spontaneous emission is further realized under strong excitation. Using the perfect hexagonal symmetric structure of the Sn doped ZnO microdisks, the whispering-gallery mode lasing with high quality factor and fine mode structure is obtained from a single microdisk.